Manajemen Anestesi Perioperatif pada Kraniotomi pada Pasien dengan Tetralogy of Fallot: Laporan Kasus - Faridatun Hasanah; I Ketut Wibawa Nada; I Gusti Ngurah Mahaalit Aribawa (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Tetralogy of Fallot (TOF) is a cyanotic congenital heart disease characterized by a right-to-left shunt, predisposing patients to complications such as brain abscess due to paradoxical emboli and chronic hypoxemia. Perioperative anesthetic management in non-cardiac neurosurgery presents a dual challenge: maintaining stable TOF hemodynamics while ensuring neuroanesthetic safety. This report describes an 18-year-old female presenting with progressive headache and a single episode of generalized seizure. Baseline oxygen saturation was 71% on 4 L/min O₂, hemoglobin 16.1 g/dL, and hematocrit 52.6%. Computed tomography revealed a right frontotemporal brain abscess with subfalcine herniation, and echocardiography confirmed classic TOF with severe pulmonic stenosis. The patient, classified as ASA III, underwent abscess-evacuation craniotomy under invasive monitoring. Anesthetic strategy included premedication with midazolam and sufentanil, induction with titrated ketamine and rocuronium, and maintenance with ≤1 MAC sevoflurane without N₂O. Protective ventilation targeted normocapnia (ETCO₂ 35–40 mmHg) and oxygen saturation of 72–78%. Hemodynamic stability was achieved using titrated vasopressors and isotonic fluids. The four-hour surgery proceeded uneventfully, with no occurrence of tet spells or arrhythmias. Key perioperative principles emphasized preserving systemic over pulmonary vascular resistance, maintaining neuroprotection through normocapnia, normothermia, and adequate analgesia, and individualized hemodynamic management. The patient was successfully extubated on postoperative day two and discharged from the ICU on day four without complications. This case underscores the critical importance of a structured, multidisciplinary approach in managing perioperative anesthesia for TOF patients undergoing neurosurgery, balancing cardiac physiology and neuroanesthetic safety.